A study on how Melaka State Fishermen’s Association (PNNM) acquires its own sources offinance other than funds provided by Malaysia Fisheries Development Board (LKIM) / Muhammad Hairil Ahmad - Ahmad, Muhammad Hairil (Faculty of Business and Management, 2011)
The reasons why the researcher accomplishes this study because want to find out the solution for the issues that arise from Melaka state fishermen’s association (PNNM). The foremost issue that the researcher has found out is the difficulty for this association to find its own source of finance to running its operation day by day. This association has to think outside the box to find and allocate the projects that can be handling or run by them and also gain profits from the projects. It is difficult for this association to allocate new business or projects because lack of experience and also don’t have big capital to enter or bid for the projects. So these associations still need help from LKIM to advise them about the projects that is good or bad for them. They also need money injections from LKIM to start the business because they don’t have enough capital to run big projects. Succeeding issue arise from this association is that the length of time to get payback from the LKIM after finish their work or projects. If PNNM wanted to enter or develop new business, they need to use their own money first than after completed the jobs they can claim the expenses from LKIM. For example, when PNNM handle courses for the LKIM executive, they need to use their money first to handle the events for the expenses such as hotel expenses, transportation, foods and others. The difficulty arises because after finish all the events, LKIM will only pay back the money to PNNM about three month after the events. This situation will make the association deficits of their money to run their other business and have to face the risk of unpaid from the LKIM.